2016
DOI: 10.1007/s10943-016-0203-1
|View full text |Cite
|
Sign up to set email alerts
|

What Mediates the Relationship Between Religious Service Attendance and Aspects of Well-Being?

Abstract: Religious service attendance predicts increased well-being across a number of studies. It is not clear, however, whether this relationship is due to religious factors such as intrinsic religiosity or due to nonreligious factors such as social support or socially desirable responding. The purpose of the present study was to examine the relationship between religious service attendance and well-being while simultaneously examining intrinsic religiosity, social support, and socially desirable responding as potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…As expected, statistically significant correlations were obtained in the predicted direction. Even though the correlation between depression and intrinsic religiosity was low, its magnitude is in agreement with the results that have been reported in the literature (Amadi et al 2016;Steffen et al 2016). Some authors point out that this relationship has the same magnitude as the relationship between sex (male vs. female) and depression, which is widely recognized in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, statistically significant correlations were obtained in the predicted direction. Even though the correlation between depression and intrinsic religiosity was low, its magnitude is in agreement with the results that have been reported in the literature (Amadi et al 2016;Steffen et al 2016). Some authors point out that this relationship has the same magnitude as the relationship between sex (male vs. female) and depression, which is widely recognized in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…We found a main effect of social support only on depressive symptomatology at t1 with higher social support being associated with fewer symptoms, but it did not buffer the effect of life events either at initial assessment or longitudinally. Our results show that the benefit of religious activity is not just simply a product of the social support that it offers but something over and above this [47].…”
Section: Discussionmentioning
confidence: 99%
“…Fenelon and Danielsen (2016) found that after disaffiliation, continued church attendance mediated any negative affect on well-being of disaffiliating. However, others have suggested that intrinsic religiosity and spiritual comfort seeking have effects that are independent from social support factors (Rasic, Robinson, Bolton, Bienvenu, & Sareen, 2011;Steffen, Masters, & Baldwin, 2017). An understanding of why these findings are contradictory is important.…”
Section: Abstract Religion/spirituality Depression Social Networkmentioning
confidence: 99%